Blockchain in Energy Transfer Management - Mäkivaara, Sofia (My University, 2019)
Blockchain is a distributed ledger technology that was first introduced a decade ago as pseudonym Satoshi Nakamoto launched Bitcoin, peer-to-peer electronic cash system to public audience. Blockchain’s inherent characteristics are decentralization, immutability, trust and transparency. Deriving from the world of cryptocurrencies, blockchains have been for a long time associated only with financial industry, but nowadays enterprises from various fields are increasingly showing interest towards the technology and investigating how they can benefit from it in their business and products. Compared to Bitcoin, enterprises have different needs regarding privacy and security and therefore enterprise blockchains emphasize different approaches in e.g. identification of members, consensus mechanism and customizability of the system structure. This thesis studies the specific field of LNG supply chains and how blockchain can contribute to energy transfer management, having the focus on the user perspective. The study was conducted as a qualitative research. In data collection phase altogether 8 semi-structured interviews were conducted with various professionals from the field of LNG, including participants from terminals, trading companies and the automation provider. The interview results helped in understanding the challenges of LNG supply chains, recognizing the supply chain participants, communication methods that are used, interconnectivity and the big picture. The relevant information in energy transfers is related to technical data, documentation and the general overview over the inventories. One of the major themes occurring in the interviews was the uncertainty about blockchain technology, how it works and what are its key benefits over more mature technologies. The key findings of this study include that there is a need for a system that increases visibility within LNG supply chains, and blockchain is a potential technology for interconnecting the different parties. There is also however need for further research on blockchain’s benefits and exploration of practical use cases. The market still needs to be educated about blockchains, and training and increasing knowledge about the topic will be in a major role in the adoption of the new technology. Because blockchains are decentralized systems, it seems more likely that enterprise blockchains are a collective effort, and not provided only by a single central entity.